Evaluate: ∫ 0 ∞ 1 + x 6 x 3 ln 2 x d x
If the result can be expressed as c d a π b , where a and c are coprime, b is an integer and d is a prime number, then find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice work V-Moy! :)
@Gabriel Merces : Care to explain how you solved the problem when the answer was incorrect?
Log in to reply
I'd Forgotten Sum of 3 of π 3
Later I Received An Email Saying that My Answer Was Incorrect , After I Make the Question Again and Seen My Error !
Log in to reply
Sorry to say, I do NOT believe you. (¬‿¬)
Log in to reply
@Anastasiya Romanova – I Cannot Make Nothing ! :D
Log in to reply
@Gabriel Merces – How about you try to answer this and make the solution? Click the problem. n = 0 ∑ ∞ 4 4 n + 1 ( 4 n + 1 ) ( − 1 ) n I'm waiting you and I hope you will be the first to make its solution.
Problem Loading...
Note Loading...
Set Loading...
Ohh, it seems the answer has already fixed it.
Here is my solution. Consider ∫ 0 ∞ 1 + x m x n − 1 d x = m sin m n π π ( * ) It can easily be proven by taking substitution y = 1 + x m 1 and the integral becomes Beta function m 1 ∫ 0 1 y 1 − m n − 1 ( 1 − y ) m n − 1 d y = m Γ ( 1 − m n ) Γ ( m n ) = m sin m n π π where the last part comes from Euler's reflection formula for the gamma function . Differentiating (*) with respect to n twice yields ∫ 0 ∞ 1 + x m x n − 1 ln 2 x d x = m 3 π 3 ( sin m n π 1 + 2 cot 2 m n π ) Substituting n = 4 and m = 6 yields ∫ 0 ∞ 1 + x 6 x 3 ln 2 x d x = 6 3 π 3 ( sin 3 2 π 1 + 2 cot 2 3 2 π ) = 3 2 4 3 5 π 3 So, a + b + c + d = 3 3 5 .